Perancangan Sistem Informasi Akuntansi Penjualan Tunai Pada CV Lan Com - Siti Farrahwati; Firmansyah Firmansyah; Eka Jumarni Fithri (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
CV Lan Com is located at Jalan Sultan M. Mansyur No.17 Bukit Lama Ilir Barat 1 Palembang, CV Lan Com is a company engaged in computer trading. This Final Report aims to design a Cash Sales Accounting Information System at CV Lan Com which still uses manual methods for cash sales systems so that the author designs cash sales using Microsoft Excel VBA. The author collects data obtained through observation, and interviews. The design is used to monitor cash sales more efficiently. In addition, this system also improves the accuracy and reliability of financial information needed for decision making, with the introduction of this Cash Sales Accounting Information System, CV Lan Com is expected to optimize the cash sales process. This system can be used for companies so that company goals can be achieved.